PEMANFAATAN TIK DALAM PEMBELAJARAN: STUDI KASUS DI MADRASAH ALIYAH NEGERI 1 BANDUNG BARAT - Mulyana Mulyana (Balai Penelitian dan Pengembangan Agama Jakarta, 2019)
This article presents the findings of research on the use of Information and Communication Technology (ICT) in learning in madrasah. The research was focused to examine factors affecting the low level use of ICT in learning in madrasah. A case study was conducted at Madrasah Aliyah Negeri (MAN) 1 in Bandung Barat Regency, West Java Province. Field research was done in February-March 2018. Data collection combines the techniques of observation, interwiews, document study, and Focus Group Discussion (FGD). This research found that in general the level of the use of ICT in learning in MAN 1 Bandung Barat is low. This low level use of ICT in learning is caused by the following factors: teachers’ ICT competency is generally still low; ICT infrastructure at the madrasah under study is limited, and there is no clear policy, both at madrasah as wells as the Office of Ministry of Religious Affairs levels, related to the effort to increase the use of ICT in learning in madrasah.